THE IMPLEMENTATION OF PROJECT BASED LEARNING (PJBL) TO IMPROVE THE STUDENTS PARTICIPATION AND LEARNING ACHIEVEMENT IN WRITING - Etika Ariyani, (Journal of Innovation Research and Knowledge, 2024)
The purpose of this Classroom Action Research (CAR) was to know whether PjBL could effectively address students participation and learning achievement as well as to identify the factors that contributed to the improvement. The research participant were 24 second grade senior high students. This Classroom Action Research (CAR) was conducted in two cycles, each cycle consisted of two meetings. The data were collected using various instruments such as interview, questionnaires, observation checklists and test conducted in the last meeting. The data were analysed using analytical scoring rubric. The result of observation showed that the students were more participate actively than before, the percentage was 52 % in cycle one and 84 % in cycle two. The result of test in cycle one showed 17 students ( 70.8 %) got higher score than minimum achievement criteria (KKM) and 7 students ( 29.2 %) failed. In cycle two, there were 21 students (87.5%) reached higher score than minimum achievement criteria (KKM) and only 3 students (12.5%) under minimum achievement criteria. It indicated that there were significant improvement which occurred in all aspects of observation. Project based learning enables students participate in classroom interaction actively, the students learn to work together, respect to other point of view, share their ideas and develop their project creatively. The research finding indicated that Project based learning (PjBL) was improve students participation and learning achievement successfully